Optimizing interactivity in health narratives: effects of message and modality interactivity on immersive narrative processes and outcomes - Lee, Hui Min (Nanyang Technological University, 2023)
Interactive narratives are a type of narrative that allows readers to make decisions for their characters at various plot points. Although such narratives are frequently used for persuasive purposes, the effects of interactivity on immersive narrative processes such as transportation and identification, and its subsequent influence on persuasive outcomes such as behavioral attitudes and intentions, have not been frequently explored. Furthermore, current studies often conceptualize and operationalize interactivity in different ways, resulting in conflicting findings regarding the persuasive effect of interactive narratives. Guided by the Theory of Interactive Media Effects (TIME), this paper, therefore, examines interactive narratives along three dimensions of interactivity: source, message, and modality interactivity. Specifically, interactive narratives are a form of customizable media (source interactivity), yet the extent of customization may be influenced by message and modality interactivity. Experiencing source interactivity also leads to perceived control and identity, crucial mechanisms for understanding the effects of interactive narratives. Thus, using a 2 (message interactivity: high/low) x 2 (modality interactivity: high/low) + 1 (control: no interactivity) between-subjects design, this study teases apart the roles of message and modality interactivity and explores the role of perceived control and identity as mediators in an interactive narrative about flu vaccination. Results showed that while message and modality interactivity did not have significant direct effects on narrative processes and outcomes, perceived identity was a significant mediator of the relationship between interactivity and flu vaccination attitudes and intention. These findings provide a deeper understanding of the mechanisms underlying the persuasive effects of interactive narratives, advancing current knowledge of its boundary conditions, and offering practical applications of interactive narratives for health-related persuasion. Theoretical and practical implications are discussed.